Coaching at work : powering your team with awareness, responsibility, and trust - Somers, Matt. (Chichester ; San Francisco, CA : Jossey-Bass, 2007)
""This book comes at a time when we are asking searching questions: How exactly do we earn the loyalty, trust and commitment of our people? How do we balance the needs of our organisations to do more with less with the need to create environments in which people can grow, develop and achieve their aspirations? The answers lie within each of those through whom so much can be achieved. This book is the key to unlocking them.""--Gareth Ford, Training & Development Manager, Atkins ""Perfect Timing! Amongst the vast selection of coaching literature, this book is powerful in 3 ways. * It has the.
How to Coach. Peak Coaching Model Pt 1-Potential & Interference -- Peak Coaching Model Pt 2 -- Performance, Learning and Enjoyment -- Peak Coaching Model Pt 3 -- Coaching and Communication -- Peak Coaching Model Pt 4 -- The Coaching Arrow -- The Model in Practice -- HOW TO APPLY COACHING -- How to Apply Coaching. Sales -- Presentations -- Personal Organisation -- Performance Review -- Career Development -- How To Implement Coaching -- How to Implement Coaching. Towards a Coaching Culture -- Implementing a Coaching Programme -- Evaluating the Programme -- Making the Business Case for Coaching.
Includes bibliographical references and index.
Print version record.
John Wiley and Sons
Keywords: Employees -- Coaching of; Teams in the workplace -- Management; Employee empowerment; Mentoring; x; Personnel -- Habilitation; BUSINESS & ECONOMICS -- Training; BUSINESS & ECONOMICS -- Mentoring & Coaching; Employee empowerment; Employees -- Coaching of; Teams in the workplace -- Management